Determination and characterization of titanium in environmental waters and sludges. Issue 1 (March 2020) - Pratiwi, A I W; Idzni, F; Dara, F; Nugraha, W C; Indriyati,; Nasir, M; Syampurwadi, A; Primadona, I
Abstract: By increasing the development of nanotechnology in recent times, there have been many commercial products contain nanomaterials. Type of nanomaterials that most widely used is Titanium dioxide (TiO2 ). These nanomaterials have been applied in various types of products, such as paints, cosmetics, etc. Unlike organic and inorganic pollutants, study and characterization of metal nanoparticle (NP) contaminants, such as TiO2 NP, have never been done in any part of Indonesia. Therefore, given the greater source of NP contaminants plus their long-term negative effects, it is deemed necessary to identify and characterize them in Indonesia. For the first case, Identification and characterization of TiO2 NP were performed in sludge and wastewater of paint and cosmetic company in the area of West Bandung district. Furthermore, the sludge and surface water of Saguling Reservoir and Cipeusing River were also analysed. Morphological and size analysis using scanning electron microscopy (SEM) and particle size analyser (PSA) revealed that most samples have NPs with a sphere shape; however, Energy Dispersive Spectroscopy (EDS) was only able to confirm the presence of titanium (Ti) element in sludge samples. Quantification of Ti (all ascribed to TiO2 NPs) in wastewater and sludge was done by graphite furnace-atomic absorption spectroscopy (GF-AAS) with high precision and accuracy. The results implied that Ti was accumulated higher in the sludge than in the water samples at the same sampling location.